Accessing Pre-Exposure Prophylaxis (PrEP): Perceptions of Current and Potential PrEP Users in Birmingham, Alabama - Rice, Whitney S. (AIDS Behav, 2019)
Limited studies to date assess barriers to and facilitators of PrEP uptake and utilization using a patient-centered access to care framework, among diverse socio-demographic groups, or in the U.S. Deep South, an area with disproportionate HIV burden. We examine perceptions of PrEP access in qualitative interviews with 44 current and potential PrEP users in Birmingham, Alabama. Participants were 32 years old on average, 66% Black, 66% gay or lesbian, 70% male, and 66% single. Perceived barriers to PrEP access included: lack of PrEP awareness and advertisement; sexuality-related stigma; time and resource constraints; and concerns about the adequacy and technical quality of PrEP services. Perceived facilitators to PrEP access were: PrEP-related information gathering and sharing; increased dialogue and visibility around PrEP; social, programmatic, and clinical support; and, lastly, self-preservation; personal motivation; and treatment self-efficacy. Results point to opportunities to address complex barriers to equitable PrEP access using multilevel and multimodal solutions.